Development of an Elastin-Like Polypeptide Carrier for an Influenza Virus Antiviral Peptide - Scinocca, Zachariah (My University, 2017)
Background: Despite the availability of a yearly vaccine and antivirals, the incidence of influenza infections remains high. The genome of the influenza virus can mutate rapidly, therefore novel influenza strains that may be resistant to the current vaccine or antivirals frequently enter the population. Because of the long production time necessary to produce a vaccine, new antivirals must be created to combat early stages of influenza outbreaks. The most effective antivirals will target a highly conserved and essential stage of virus replication. The influenza RNA-dependent RNA polymerase is a heterotrimeric complex composed of three subunits: PA, PB1, and PB2. The three components of the polymerase interact through well-defined domains and are essential for viral replication. Previously, influenza replication has been inhibited using a small synthetic peptide that mimics the interaction domain between PA and PB1 and inhibits the formation of the heterotrimeric complex. Problem and Hypothesis: Although the peptide could inhibit influenza replication, synthetic peptides are costly to produce and are not a viable option for large-scale production. This problem can often be overcome by attaching the peptide to a highly soluble carrier protein. We hypothesize that influenza replication can be inhibited by attaching a peptide, that mimics the binding domain between the PA and PB1 subunits, to a human elastin-like polypeptide (ELP) carrier protein. Methods and Results: The peptide and a nuclear localization sequence was genetically linked to a maltose binding protein (MBP) or ELP carrier protein. The MBP construct was purified by affinity chromatography using FPLC. A high yield of the ELP construct was obtained using inverse transition cycling, a method unique to ELPs because of their temperature-dependent solubility. The ELP construct was designed to be soluble at physiological temperature to limit cellular toxicity due to protein aggregation. The cytotoxicity of the ELP construct was assessed by monitoring the growth of A549 cells, a human lung epithelial cell line. The ELP construct did not have any adverse effects on A549 cell growth. Both constructs could localize to cell nuclei using their respective nuclear localization sequences and could also interact with the PA subunit, demonstrating their potential to inhibit influenza replication. Despite this, only the MBP construct was able to inhibit the replication of influenza. The MBP construct could inhibit the replication of both the H1N1 and H3N2 subtypes of influenza, indicating the recombinant protein had cross-strain activity. Conclusion: Linking a small peptide to carrier protein can result in high protein yields, however a carrier protein must be chosen that will maintain the peptides’ therapeutic activity. In this study, a small anti-influenza peptide inhibited influenza replication when attached to an MBP carrier protein, however was not able to inhibit influenza replication when attached to an ELP carrier protein. Although the peptide was ineffective when attached to this particular ELP carrier protein, different ELP proteins of various lengths and compositions may still be effective carrier proteins for an antiviral peptide.
Keywords: Influenza; Antiviral; Peptide; Elastin-like Polypeptide